EXPOSURE TO CARBONIC GAS ENRICHED ATMOSPHERE OR ELECTRICAL WATER BATH TO STUN OR KILL CHICKENS - Nicolau,JP (2015)
ABSTRACTThe objective of this study was to compare the effects of two methods (electrical water bath or carbonic gas atmosphere) for stunning or killing broiler chickens prior to bleeding on weight loss due to bleeding and meat traits. A completely randomized design with 2 x 2 factorial arrangement (electrical or gas system x stunning or killing) was applied. The time required for stunning and killing and the birds' behavior were evaluated for the gas exposure method. The birds killed by the electrical method retained more blood than those killed by the exposure to gas and, therefore, presented redder meat. The exposure to 10 to 15% CO2 atmosphere caused discomfort reactions in 100% of birds, and the intensity of reaction presented a wide variation: 35% for weak reaction, 40% for intermediate reaction, and 25% for strong reaction. The time required to stun or kill the birds by CO2 exposure varied from 28 to 97 seconds and from 42 to 158 seconds, respectively. It was concluded that the time required to stun or to kill the birds by CO2 exposure widely varied and caused discomfort reactions; however, meat traits were not influenced by the methods used in this experiment.